2004
DOI: 10.1051/vetres:2004015
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection ofCulicoidesspp. andCulicoides imicola, the principal vector of bluetongue (BT) and African horse sickness (AHS) in Africa and Europe

Abstract: -Bluetongue (BT) and African Horse Sickness (AHS) are infectious arthropod-borne viral diseases affecting ruminants and horses, respectively. Culicoides imicola Kieffer, 1913, a biting midge, is the principal vector of these livestock diseases in Africa and Europe. Recently bluetongue disease has re-emerged in the Mediterranean Basin and has had a devastating effect on the sheep industry in Italy and on the islands of Sicily, Sardinia, Corsica and the Balearics, but fortunately, has not penetrated onto mainlan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 24 publications
0
52
0
Order By: Relevance
“…As correct identification of disease vectors is essential in transmission risk assessment, recent efforts have centred upon developing molecular and morphological tools that allow a reliable discrimination between similar species of the Obsoletus group (Cêtre-Sossah et al, 2004;Pagès & Sarto i Monteys, 2005;Mathieu et al, 2007;Nolan et al, 2007;Augot et al, 2010;Nielsen & Kristensen, 2011). In spite of the advantages of employing morphometrics in cryptic species identification and the widespread use of this methodological approach in other biological disciplines, few studies have attempted to discriminate between similar species of Culicoides using multivariate analysis of continuous traits (exceptions are Pagès et al, 2009;Augot et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…As correct identification of disease vectors is essential in transmission risk assessment, recent efforts have centred upon developing molecular and morphological tools that allow a reliable discrimination between similar species of the Obsoletus group (Cêtre-Sossah et al, 2004;Pagès & Sarto i Monteys, 2005;Mathieu et al, 2007;Nolan et al, 2007;Augot et al, 2010;Nielsen & Kristensen, 2011). In spite of the advantages of employing morphometrics in cryptic species identification and the widespread use of this methodological approach in other biological disciplines, few studies have attempted to discriminate between similar species of Culicoides using multivariate analysis of continuous traits (exceptions are Pagès et al, 2009;Augot et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies (Dallas et al 2003;Li et al 2003;Cêtre-Sossah et al 2004;Wörheide et al 2004;Perrin et al 2006) dealing with a similar problem found the noncoding genetic region of the internal transcribed spacer 1 (ITS-1) of the mitochondrial ribosomal DNA and mitochondrial cytochrome c oxidase subunit 1 (COI) to be highly promising in order to establish a reliable polymerase chain reaction (PCR)-based method for species identification.…”
Section: Introductionmentioning
confidence: 99%
“…Using highly specific and sensitive oligonucleotides based on the ITS1 ribosomal DNA sequences, C. imicola has been identified in mixed pools of several European Culicoides spp. (Cêtre-Sossah et al 2004). Sequencing the ITS1 rDNA of 32 species of Culicoides for a phylogenetic analysis, C obsoletus, C. scoticus, and C. imicola clustered together, clearly separated from C. nubeculosus, C. puncticollis, and C. variipennis, the latter being classified as members of the Obsoletus complex or as members of the subgenus Monoculicoides (Perrin et al 2006).…”
Section: Discussionmentioning
confidence: 97%
“…In ceratopogonids, sequences of the nuclear internal transcribed spacer (ITS) or the mitochondrial cytochrome oxidase subunit I (COI) have been used (Cêtre-Sossah et al 2004;Meiswinkel et al 2004;Pages and Sarto i Monteys 2005;Nolan et al 2007). In the present investigation, we used oligonucleotides suggested to be specific for COI of two species of the Obsoletus complex, Culicoides obsolteus s.s., and C. scoticus (Pages and Sarto i Monteys 2005).…”
Section: Introductionmentioning
confidence: 99%